On Indexation and Contract Length - Gray, Jo Anna (Journal of Political Economy, 1978)
This paper examines the joint determination of labor contract length and the degree of wage indexation in a neoclassical model modified to incorporate short-term wage rigidities and uncertainty, both real and monetary. A number of propositions are demonstrated. Optimal indexing may not insulate the real sector from unanticipated monetary shocks. For any given degree of indexing, contract length decreases with the level of uncertainty and increases with the cost of contracting. If indexing is costly, indexing provisions will appear only in longer contracts. The proportion of contracts indexed will increase with the variance of monetary disturbances. Finally, monetary variability may cause resource misallocation among industries. Some related policy implications are noted.